Políticas de información y discapacidad: Nuevos retos para la integración - Burgos Bordonau, Esther (Revista General de Información y Documentación, 2006)
Balance and analysis of the Academic Sessions that under the title: «Information Policies and Disability: new challenges for integration» were celebrated in the premises of the School of Librarianship and Documentation of the UCM from 9 upto the 10th march 2006. In this paper we analyze the different lectures given by the professionals present in the Sessions as well as the most relevant information regarding these matters given in the different discussion groups. Finally a reflection of the couple of days of work is made known and an invitation to the readers to think about this particular matter in the spanish university and our daily lives.